A study on the ability transfer of Chinese swimmers in single middle and short distance events - Shang, M.; Cheng, Y. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: According to statistics, the number of medals in the four strokes of 50m, 100m and 200m accounts for 77% of the medals at the World Championships. Swimmers usually excel in 1-2 of these distances, and outstanding swimmers are able to achieve all-around development by excelling in 3 distances. However, it is rare for top swimmers to achieve excellence in a single event at 50m, 100m and 200m distances and win medals in all of them. At the 2023 World Championships, Chinas breaststroke swimmer Qin Haiyang achieved a historic achievement in the 50m, 100m and 200m breaststroke events, creating a trio of titles. At the same World Championships, Kaylee McKeown dominated the backstroke events, winning all three titles. These achievements highlight the fact that competing and excelling in multiple events has become a new competitive trend. This study delves into the migration of Chinese swimmers ability to compete in a single short- and middle-distance event, and promotes multi-event participation and multidimensional skill enhancement in swimmers, which is believed to enhance the overall competitiveness and depth of talent in the sport. METHODS: The search results were analyzed on China Knowledge and Google Scholar using the keywords "swimming ability", "transfer learning" and "multisport development", combined with interviews with Chinese swimming team coaches and researchers. The results were analyzed. RESULTS: During the period 2016-2023, two Olympic Games and four World Championships were held. In the 2016 Rio Olympics, there were six champion-cum-athletes; in the 2017 Budapest World Championships, there were 12 champion-cum-athletes; in the 2019 Gwangju World Championships, there were 13 champion-cum-athletes; in the 2021 Tokyo Olympics, there were 14 champion-cum-athletes; in the 2022 Budapest World Championships, there were 17 at the 2022 World Championships in Budapest; and 17 at the 2023 World Championships in Fukuoka. As of February 2024, there are 17 times in the history of the World Championships in the 50-100-200 meters can achieve both medals, of which the number of athletes in the 2019 and 2023 World Championships in the 50-100-200 meters at the same time to win medals are three, which reflects that in recent years the swimming world of the ability of athletes to participate in multiple events in the level of training to obtain a greater improvement. In particular, Chinas Luo Xuejuan, Zhang Yufei and Qin Haiyang were among the 17 people mentioned above. In terms of strokes, there are 6 breaststroke, 4 freestyle, 3 backstroke and 1 butterfly, reflecting that breaststroke is easier to migrate in ability. 2023 World Championships at the same time, there are 2 people at the same time to take the small event Grand Crown. CONCLUSION: The study of kinematic characteristics, departure and stroke kinetics characteristics, energy metabolism characteristics, and specialized fitness characteristics of short- and middle-distance swimmers is the key to solving the synergistic develop